1984
DOI: 10.1007/bf01059554
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the volumes of distribution of basic drugs in humans based on data from animals

Abstract: The apparent volume of distribution-after distribution equilibrium and the ratio of distributive tissue volume to the unbound fraction in the tissue (VT/fuT) of 10 weak basic drugs, i.e., chlorpromazine, imipramine, propranolol, disopyramide, lidocaine, quinidine, meperidine, pentazocine, chlorpheniramine, and methacyclin were compared in animal species and humans. In these two parameters, a statistically significant correlation between animals and humans was obtained, when the parameters were plotted on a log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 36 publications
5
70
0
Order By: Relevance
“…A second clear trend was that correction of rat P tp data for interspecies differences in plasma protein binding yielded better predictions compared with when binding differences were ignored (84% versus 53% within 2-fold). This observation was anticipated because in scaling tissue distribution from rat to human, the unbound human P tp values are generally assumed to be identical to those of rat (Sawada et al, 1984). Nevertheless, in the case of basic drugs, the accuracy of this assumption remains uncertain since electrostatic interactions with acidic phospholipids have been identified as a major factor controlling tissue distribution (Rodgers et al, 2005b), and an interspecies variability in the acidic phospholipids has been indicated (Rodgers et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second clear trend was that correction of rat P tp data for interspecies differences in plasma protein binding yielded better predictions compared with when binding differences were ignored (84% versus 53% within 2-fold). This observation was anticipated because in scaling tissue distribution from rat to human, the unbound human P tp values are generally assumed to be identical to those of rat (Sawada et al, 1984). Nevertheless, in the case of basic drugs, the accuracy of this assumption remains uncertain since electrostatic interactions with acidic phospholipids have been identified as a major factor controlling tissue distribution (Rodgers et al, 2005b), and an interspecies variability in the acidic phospholipids has been indicated (Rodgers et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…For lipophilic and highly protein-bound compounds, it has been assumed that for adipose tissue, RA equals 0.15, whereas for nonadipose tissue, RA equal 0.5 (Ellmerer et al, 2000;Poulin and Theil, 2002). Finally, rat and human V ss values were calculated by Gastroplus software according to the equation of Sawada et al (1984) in which V ss equals the plasma volume in addition to the sum of each P tp multiplied by its respective tissue volume.Prediction of Human and Rat P tp and V ss : Method Vd2. For rat P tp and V ss , experimental rat P tp values were determined under in vivo conditions (single oral or intravenous dose) as the ratio of the AUC calculated over a minimum of five time points, assuming pseudoequilibrium.…”
mentioning
confidence: 99%
“…Clearance and V ss were calculated as described below for input into the disposition part of the model. V ss was calculated from predicted P tp (tissue to plasma partition coefficient) [5]. Predicted values of P tp for each tissue compartment were obtained from drug-specific physicochemical parameters using the tissue composition-based equation described by Rodgers et al [6,7].…”
Section: Pbpk Model Verification In the Ratmentioning
confidence: 99%
“…Data collection R b and f p values were collected for 96 compounds in humans and 60 compounds in rat, mainly from Goodman & Gilman's The Pharmacological Basis of Therapeutics; Tenth Edition and from reports on the prediction of pharmacokinetic parameters [6][7][8][9][10][11][12][13][14][15][16]. Prolog D (log D) was calculated using the Pallas software for Windows (version 1.1; Infocom, Berkshire, UK).…”
Section: Theorymentioning
confidence: 99%